2016
DOI: 10.1177/0022034516653922
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of TMD Diagnosis

Abstract: This review explores the principles and process associated with the diagnosis of temporomandibular disorders (TMDs). TMD diagnosis has evolved substantially over the past 25 y. Previously, diagnosis focused solely on aberrations in oral structures, largely without empirical evidence. The Research Diagnostic Criteria for TMD (RDC/TMD) were developed on core principles of 1) a dual-axis system reflecting the biopsychosocial model, 2) a clear operationalization for reliability, and 3) the allowance of multiple di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
193
0
18

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(252 citation statements)
references
References 53 publications
4
193
0
18
Order By: Relevance
“…Experts in the field of orofacial motricity claim that OMD may not be the cause of TMD, but the more severe the OMD, more difficult its resolution without approaches that specifically target myofunctional orofacial re-education or rebalancing 8 . The presence of comorbidities can be one complication or nonresolution factors of TMD after treatment, that is, another problem that may occur in parallel with what is being treated, that has some relation and influence on its severity 2,3,20,21 . In this case, it seems that the OMD was a TMD comorbidity since we cannot claim that it was the triggering factor, but its presence contributed to the aggravation and maintenance of TMD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Experts in the field of orofacial motricity claim that OMD may not be the cause of TMD, but the more severe the OMD, more difficult its resolution without approaches that specifically target myofunctional orofacial re-education or rebalancing 8 . The presence of comorbidities can be one complication or nonresolution factors of TMD after treatment, that is, another problem that may occur in parallel with what is being treated, that has some relation and influence on its severity 2,3,20,21 . In this case, it seems that the OMD was a TMD comorbidity since we cannot claim that it was the triggering factor, but its presence contributed to the aggravation and maintenance of TMD.…”
Section: Discussionmentioning
confidence: 99%
“…As the sessions evolved with improvement in the patient's conditions, strategies were included and trained to balance chewing and swallowing and to promote a more intelligible phonoarticulation, in addition to the mandibular rest with free mandibular functional space preserved (step 3 orofacial myofunctional therapy) ( Table 1). After 13 weekly sessions, other 10 sessions were carried for 6 fortnightly sessions and 4 monthly ones, in which were included in the therapeutic process complementary mindfulness practices that constitute an important group of meditation practices used as a tool to reduce stress and anxiety, also being recognized to contribute in the reduction of painful pictures 2,13 . Since the phonological approach was directed to the stomatognathic system, the exercises, guided by the therapist, focused on the rhythm of breathing and attention to the orofacial structures (anchor of the mindfulness practice: aspect or object to which the targeting -or focus -is exercised).…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…The TMD affects psychological conditions and masticatory ability, influencing the oral health-related quality of life (OHRQoL) of individuals 3 . Subjective indicators used for general and oral health showed that TMD plays an important role on the quality of life and, despite the numerous methods used to assess OHRQoL and TMD [4][5][6] , the assessment of elderly subjects is rare.…”
Section: Introductionmentioning
confidence: 99%